THE EFFECT OF COMPANY SIZES AND PROFITABILITY ON AUDIT REPORT LAG IN AUTOMOTIVE COMPANIES THAT LISTED IN INDONESIA STOCK EXCHANGE - Sitti Murniati (Patria Artha Journal of Accounting dan Financial Reporting, 2019)
This study aims: 1) to determine and analyze the effect of company size on audit report lag on Automotive companies listed on the Indonesia Stock Exchange, and 2) to determine and analyze the effect of profitability on audit report lag on Automotive companies listed on the Indonesia Stock Exchange. Data collection was carried out through documentation techniques in the form of financial statements for 5 years from 2013 to 2017 with the type of data pooling research. Automotive company research subjects listed on the Indonesia Stock Exchange. The data analysis method used in this study is the multiple regression equation. The results show that 1) Large companies generally have a good internal control system and are closely monitored by investors, capital supervisors, and the government so as to reduce errors in the presentation of financial statements and facilitate auditors in conducting the audit process, so that the completion of the audit will be faster, and 2) Companies that have high or low profitability do not affect the timeliness in submitting financial statements, where companies that have a higher level of profitability do not need time in auditing financial statements as soon as expected